‘Green Wall Rating’: A Methodology to Evaluate Sustainable Development by Implementing Green Wall Model - Tiwari, Neeraj Kumar; Srivastava, Ankit Kumar (Discoveries in Agriculture and Food Sciences, 2014)
The modern technology has changed the life of human being. Rapidly changing technology develops many kind of development approaches and products which makes the life easier and comfortable but they have also a negative impact on human beings as well as on the environment, In this paper a green wall rating methodology is being introduced. The protocols used in this rating methodology, a developer can rate any product or process well in terms of sustainability. Further green wall rating (GWR) can be measured with the help of sustainable development qualities. About the essential qualities for sustainable development has been discussed in our earlier publication (Srivastava, et. al., 2014). On the basis of conceptual hypothesis the practical value of GWR has to be set between 2.00 to 4.00 units. For being a sustainable process or product it must contains at least 2.00 green wall rating.